Revenue Management Capability and Front Office Financial Control in Optimizing Rooms Division Financial Performance: The Role of Digital Reservation Integration in Indonesian Hotels - Nor Ismawanto Choirudin; Ananta Budhi Danurdara; Wanti Arum Wanti; Rudy Parlindungan Siahaan (AIBPM Publisher, 2026)
This study examines the effects of revenue management capability and front office financial control on rooms division financial performance in Indonesian hotels, with digital reservation integration positioned as both a direct predictor and moderating variable. A quantitative approach was employed using a cross-sectional survey involving 250 hotel operational personnel from Indonesian hotels implementing digital reservation systems and property management systems (PMS). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that revenue management capability positively affects rooms division financial performance (? = 0.318; p 0.001), followed by front office financial control (? = 0.284; p 0.001) and digital reservation integration (? = 0.301; p 0.001). The findings further reveal that digital reservation integration significantly strengthens the relationships between revenue management capability and rooms division financial performance (? = 0.167; p 0.001) and between front office financial control and rooms division financial performance (? = 0.153; p = 0.001). The model explains 71.4% of the variance in rooms division financial performance (R² = 0.714). The findings confirm that hotel financial performance increasingly depends on the integration between pricing capability, operational financial control, and digitally integrated reservation systems.